2005
DOI: 10.1203/01.pdr.0000169983.40758.7b
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical and Molecular Genetic Study of Hypophosphatemic Rickets in Children

Abstract: X-linked hypophosphatemic rickets (XLH), autosomal dominant hypophosphatemic rickets, hereditary hypophosphatemic rickets with hypercalciuria, and tumor-induced osteomalacia share clinical and biochemical features, and are collectively referred to as hypophosphatemic rickets (HR). Recently, the molecular bases of HR were elucidated. A review of medical records and mutational analyses of the PHEX and FGF23 genes were performed on 17 unrelated Korean children with HR. The male-to-female ratio was 3:14, and 5 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
64
3
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 32 publications
9
64
3
3
Order By: Relevance
“…These findings are similar to studies from the Republic of Korea and north India, 5,12 which found a greater number of female patients (82% and 70.5% respectively) than male patients with hypophosphataemic rickets. In these studies, a positive family history was noted in 29% and 35.3% respectively.…”
Section: Discussionsupporting
confidence: 90%
“…These findings are similar to studies from the Republic of Korea and north India, 5,12 which found a greater number of female patients (82% and 70.5% respectively) than male patients with hypophosphataemic rickets. In these studies, a positive family history was noted in 29% and 35.3% respectively.…”
Section: Discussionsupporting
confidence: 90%
“…The overall median detection rate of gene mutations reported in previous studies comprising 15 or more HR probands was 66% (range 43-100%), 20,[27][28][29][30][31][32][37][38][39][40][41] in familial probands 66% (44-100%), and in sporadic probands the detection rate was 50% (29-100%). 20,[27][28][29][30]32,37,38 In our study, the MLPA analysis added three PHEX mutations not identified by PCR, dHPLC or sequencing, thus increasing our overall detection rate from 78 to 88%, in familial probands from 67 to 83% and in sporadic probands from 83 to 92%. Our high detection rate of gene mutations, especially among the sporadic patients, may also be due to the robust inclusion/ exclusion criteria of this study.…”
Section: Discussionmentioning
confidence: 99%
“…In XHR, hyperphosphaturia derives from mutations in the PHEX gene (Phosphate regulating gene with homologies to Endopeptidases on the X-chromossome) (1)(2)(3)(13)(14)(15)(16). This gene, whose locus is Xp22.1, encodes a membrane endopeptidase (Znmetaloprotease), called Phex, mainly expressed in bone and teeth.…”
Section: Hypophosphatemic Rickets -Pathophysiologymentioning
confidence: 99%
“…HR comprises a set of disorders, inherited and acquired, that shares a common pathophysiology: diminished phosphate reabsorption in renal tubules (3,(13)(14)(15). This process, established by an impaired phosphorus renal handling, leads to chronic hyperphosphaturia and hypophosphatemia, which are associated to unsuitable normal or low levels of 1,25(OH) 2 VitaminD 3.…”
mentioning
confidence: 99%
See 1 more Smart Citation